Development of virtual pH analyzer with PID gain scheduling control method / Murniwati Ab. Manan - Ab. Manan, Murniwati (2013)
This paper presents the development of virtual pH analyzer that equipped with PID Gain Scheduling control method. This project is implemented using LabVIEW and the functionality of the instrument is tested. In this study, the PID Gain Scheduling was tested using ITAE tuning method. The functionality of virtual pH analyzer was evaluated in term of percentage overshoot (%OS). The outcome of the project is the flexible instrument that replaces the traditional instrument for pH measurement and control.